TECHNOLOGY-BASED SUPERVISION: OPTIMIZING THE ROLE OF SUPERVISION IN THE DIGITAL LEARNING ERA - Mahmudi, Rois; Ulfa, Vina Mardiana; Rofiq, Ainur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to optimize the role of supervision in the era of technology-based digital learning. The object of this research is Technology-Based Supervision: Optimizing the Role of Supervision in the Digital Learning Era at SMA Darussalam Blokagung Banyuwangi East Java. In this research, the method used is qualitative with a case study approach to examine the effectiveness of technology-based supervision at SMA Darussalam Blokagung, Banyuwangi, East Java. The source of informants in this study consisted of the Quality Control Team (TPM), the principal, and teachers at SMA Darussalam Blokagung Banyuwangi, East Java. Data collection techniques in this study include observation, interviews, and documentation, which aim to gain a comprehensive understanding of the effectiveness of technology-based supervision at SMA Darussalam Blokagung Banyuwangi, East Java. Data analysis in this study used the data analysis model proposed by Miles and Huberman, which consists of three main steps: data reduction, data presentation, and conclusion drawing. The results of this study are the increased effectiveness of supervision through digital tools, the ability of supervisors to monitor the development of learning innovations globally and the improvement of teacher competence in technology through digital supervision.